PRAISE THE LORD IN PSALM 150:1-3 - Woy, Jones Ted Lauda; Tauran, Edgar Willem Melko (Klabat Theological Review; Vol 4 No 2 (2024): Klabat Theological Review, 2024)
The book of Psalms, or Psalter, contains some of the most cherished Bible passages, derived from its title in the Septuagint as Psalmoi, meaning songs to be sung with stringed instruments. It is attributed to various authors, including David, Asaph, Korah, Moses, Heman, Ethan, Solomon, and Jeduthun. This study aims to explore the possible meanings and translations of the text by applying morphological and syntactical analyses. It will examine the context, the role and function of the text, analyze each word's lexical meaning, and ultimately provide a literal translation and interpretation based on these findings. Keywords: Psalm, Worship, Music, Hallelujah.